1994
DOI: 10.1084/jem.180.6.2359
|View full text |Cite
|
Sign up to set email alerts
|

The germfree state prevents development of gut and joint inflammatory disease in HLA-B27 transgenic rats.

Abstract: A number of inflammatory disease states occur with greatly increased frequency in individuals inheriting the human major histocompatibility complex class I allele HLA-B27. In a minority of cases, namely those with B27-associated reactive arthritis, there is good evidence that the disease state is triggered by infection with an enteric or genitourinary bacterial pathogen. For the majority of B27-associated disease, no definite pathogenetic role for bacteria has been established. However, in these latter cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
524
1
18

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,041 publications
(557 citation statements)
references
References 19 publications
14
524
1
18
Order By: Relevance
“…Occasional spondylitis has also been seen in histologic specimens of tail vertebrae (9). Neither gastrointestinal inflammation nor arthritis develop in these B27-transgenic rats when raised under germ-free conditions, whereas epididymo-orchitis and skin lesions are found (11,12). On the inbred LEW background, the prevalence of colitis in the B27-transgenic rats approaches 100%, whereas arthritis occurs in ϳ40% of the males and in a lower proportion of the females, and the onset of arthritis follows the onset of diarrhea by an average of ϳ1 month (13).…”
mentioning
confidence: 89%
“…Occasional spondylitis has also been seen in histologic specimens of tail vertebrae (9). Neither gastrointestinal inflammation nor arthritis develop in these B27-transgenic rats when raised under germ-free conditions, whereas epididymo-orchitis and skin lesions are found (11,12). On the inbred LEW background, the prevalence of colitis in the B27-transgenic rats approaches 100%, whereas arthritis occurs in ϳ40% of the males and in a lower proportion of the females, and the onset of arthritis follows the onset of diarrhea by an average of ϳ1 month (13).…”
mentioning
confidence: 89%
“…Various high-copy number B27 transgenics develop disease while HLA-B7 controls do not [52]. The subsequent application of the HLA-B27 transgenic rats to investigate the factors contributing to disease demonstrates some of the potential benefits of a transgenic approach for elucidating disease mechanisms [53].…”
Section: Hla Transgenics Models For Disease Studies and Epitope Mappingmentioning
confidence: 99%
“…Evidence for the role of the bacterial flora in the induction of experimental colitis is that germ-free or specific pathogen-free animals develop no or less severe inflammation. This was shown in several colitis models, such as indomethacin-induced colitis [11], HLA-B27 transgenic rats [12], IL-2 knockout mice [2] and IL-10 knockout mice [13]. Recently, Brandwein et al [14] showed that C3H/HeJBir mice, which spontaneously develop colitis, produce antibodies to bacterial antigens of the enteric flora.…”
Section: Introductionmentioning
confidence: 98%